Pelatihan dan Pendampingan Pemasaran Batik di Lendah Kulonprogo Daerah Istimewa Yogyakarta - Gunawan, Barbara; Gunawan, Yordan (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this community service program is to provide production and marketing assistance to Partners, namely Aricha Batik, which produces contemporary batik types. The problems that exist in the production aspect are the motifs and patterns of batik that are less diverse, whereas for the marketing aspect Partners do not have a nameplate, conventional marketing mechanisms, packaging that is still simple, and do not make financial reports. To solve this problem, the servant provides several solutions, from the aspect of production, the servant offers a solution to the Partner to produce the type of batik that is being sought by potential potential customers; while from the marketing aspect, the servant offers a solution to make a signboard at the production location, make a gift box, a more attractive logo, market through social media. Servants also offer solutions in the form of assistance in preparing simple financial statements. The method used to solve partner problems is to hold discussions, trainings, create signboards, brands, exclusive gift box packaging, and create social media accounts. The results of this community service activity are the increasing diversity of batik motifs, the presence of attractive logos (brands), name boards installed, exclusive gift boxes, paper and plastic bags, marketing training, training in preparing financial statements, and forming social media accounts to market products. . Besides providing production and marketing assistance, the servants also offer products to potential consumers. From these activities several office uniform orders took place, which resulted in an increase in sales revenue.